A Modified MCT-Based Ketogenic Diet Increases Plasma β-Hydroxybutyrate but Has Less Effect on Fatigue and Quality of Life in People with Multiple Sclerosis Compared to a Modified Paleolithic Diet: A Waitlist-Controlled, Randomized Pilot Study. (2nd January 2021) - Lee, Jennifer E.; Titcomb, Tyler J.; Bisht, Babita; Rubenstein, Linda M.; Louison, Rebecca; Wahls, Terry L.
Abstract: Objective: To investigate the feasibility of a modified MCT-based ketogenic diet and its impact on plasma β-hydroxybutyrate and MS outcomes compared to a modified Paleolithic diet and usual diet in people with Multiple Sclerosis (MS). Methods: Fifteen individuals with MS were randomized to 3 groups: 1) modified Paleolithic diet (Paleo; n  = 6); 2) medium-chain triglyceride (MCT)-based ketogenic diet that included coconut as a fat source (Keto; n  = 5); or 3) usual diet (Control; n  = 4). Participants had blood drawn every 4 weeks to monitor nutritional ketosis. Participants completed 4-day weighed food records, measures of disability, fatigue, quality of life (QoL), cognitive function, and physical function at baseline and 12-weeks. Results: Macronutrient intake significantly shifted toward a ratio indicative of a ketogenic diet in the Keto group at 12 weeks. Similarly, plasma β-hydroxybutyrate indicated nutritional ketosis in the Keto group, whereas neither macronutrient intake nor plasma β-hydroxybutyrate indicated nutritional ketosis in the Paleo and Control groups. The Paleo group had significant within group reductions in fatigue scores and maintained cognitive function scores compared to the Control group. The Keto group had significant reductions in fasting glucose and insulin compared to baseline values; however, no clinical outcomes significantly changed. Conclusions: Participants consuming the MCT-based ketogenic diet achieved nutritional ketosis; however, it was not associated with significant clinical improvement in this study whereas the modified Paleolithic diet was associated with significant clinical improvements. Larger randomized controlled trials are needed to determine the safety and efficacy of the modified Paleolithic and MCT-based ketogenic diets on MS.